Action reflection learning solving real business problems by connecting learning with earning - Rimanoczy, Isabel, 1956-; Turner, Ernie, 1942- (Davies-Black Pub., 2008)
Built on a solid foundation of adult learning theory and action learning methodology. Action Reflection Learning delivers a next-generation, multidisciplinary approach that will take your teaching and facilitating interventions to a new level of excellence.